1983
DOI: 10.3758/bf03197665
|View full text |Cite
|
Sign up to set email alerts
|

Associative asymmetry, availability, and retrieval

Abstract: Associative frequency, the ease with which a word comes to mind in free association, is taken as a measure of general response availability. As expected from this view, in both controlled experiments and in reanalyses of previously published correlational data, high associative frequency words were judged to be more familiar and were easier to recall but harder to recognize than low associative frequency words, even with meaningfulnees, imagery, length in letters, and frequency excluded as factors. When used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Although there may be other factors, not included in our set of variables, that contribute to familiarity ratings, our results show clearly that familiarity ratings cannot be used as a substitute for objective word frequency measures (Rubin, 1976), since other factors, such as word learning age, contribute to the familiarity ratings (see also Rubin, 1983). Indeed, not only does AOA independently predict familiarity ratings, but in our study it was more highly correlated with the familiarity measure than were either of the frequency counts.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although there may be other factors, not included in our set of variables, that contribute to familiarity ratings, our results show clearly that familiarity ratings cannot be used as a substitute for objective word frequency measures (Rubin, 1976), since other factors, such as word learning age, contribute to the familiarity ratings (see also Rubin, 1983). Indeed, not only does AOA independently predict familiarity ratings, but in our study it was more highly correlated with the familiarity measure than were either of the frequency counts.…”
Section: Discussionmentioning
confidence: 92%
“…Brown (1984) found that rated familiarity was more highly correlated with spoken than with written word frequency and was most highly correlated with rated word age-ofacquisition. Rubin (1983) found that associative frequency predicted rated familiarity, although his analysis included no measure of age-of-acquisition. Accordingly, we examined the extent to which various factors contribute to variance in familiarity ratings by using rated familiarity as the dependent measure in multiple regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragment theory therefore predicts that targets and cues are interchangeable. This distinctive and testable assumption of fragment theory, though it is not central to our main point and though it on occasion appears to be false (Anderson & Bower, 1980, p. 237;Rubin, 1983), is maintained in order to explore the pervasive role of uniqueness. In particular, we claim that the symmetry assumed by fragment theory can hold only if all possible cues in a stimulus (i.e., all components) are uniquely related to all possible targets (i.e., all other components), which implies that each component can appear in only one stimulus.…”
Section: Five Studies With Nonunique Cues That Would Not Support Fragmentioning
confidence: 99%
“…For instance, Kintsch and van Dijk (1978) offer a quantitatively successful model of why particular units of text are remembered or forgotten. Not as much formal theoretical work has been undertaken with lists, but empirically it appears that imagery and associative frequency are the major factors in predicting which words are recalled (Rubin, 1980(Rubin, , 1983. Still lacking, however, is a formal theory of why the rank order is stable over some changes in conditions, but not others.…”
Section: Discussionmentioning
confidence: 99%